A ps level actively mode-locked Ho:Sc2SiO5 laser at 2112.1 nm resonantly-pumped by Tm fiber laser. (4th December 2017) - Xiao, You-hong; Mu, Yan-long; Yang, Le-le; Jiang, Zi-yin; Yang, Xiao-tao
Abstract: An actively mode-locked Ho:SSO laser was reported for the first time, which was resonantly-pumped by a Tm-doped fiber laser. Both performance of continuous wave (CW) mode and continuous wave mode-locked (CWML) were researched in this paper. For the CW mode, the maximum output power of the 2.88 W with the central wavelength of 2112.1 nm was achieved, when the absorbed pump power was 16.2 W. The optical-optical conversion efficiency was 17.8%. Compared with the CW mode, the maximum laser output power of CWML mode was a little lower, which was 2.72 W corresponding to an optical-optical conversion efficiency of 16.8%. However, the laser output wavelength of the CWML mode was the same as the CW mode focus on 2112.1 nm. The repetition rate of CWML pulse was measured to be 81.88 MHz with the single pulse energy of 33.2 nJ and pulse duration of 282.4 ps. The peak-power was 117.6 W.